2004
DOI: 10.1158/1535-7163.1427.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of cyclin-dependent kinase 4/6 by PD 0332991 and associated antitumor activity in human tumor xenografts

Abstract: PD 0332991 is a highly specific inhibitor of cyclin-dependent kinase 4 (Cdk4) (IC50, 0.011 μmol/L) and Cdk6 (IC50, 0.016 μmol/L), having no activity against a panel of 36 additional protein kinases. It is a potent antiproliferative agent against retinoblastoma (Rb)-positive tumor cells in vitro, inducing an exclusive G1 arrest, with a concomitant reduction of phospho-Ser780/Ser795 on the Rb protein. Oral administration of PD 0332991 to mice bearing the Colo-205 human colon carcinoma produces marked tumor regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
186
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,107 publications
(198 citation statements)
references
References 81 publications
8
186
0
4
Order By: Relevance
“…Tumors expressing ER and/or PR are termed hormone receptor positive (HR+) or luminal BC, accounting for over 70% of all BC; tumors expressing HER2 are called HER2-enriched BC, accounting for 10-20% of BC; and tumors that do not express ER, PR and HER2 are called triple negative (TN) BC, accounting for 10-15% of BC ( 30 , 73 ). When CDK4/6i were developed and tested in preclinical studies, cell lines and xenografts representing the luminal BC subtype were shown to be most susceptible to proliferation arrest and tumor shrinkage ( 31 , 74 ).…”
Section: Cdk-i and Endocrine Therapymentioning
confidence: 99%
“…Tumors expressing ER and/or PR are termed hormone receptor positive (HR+) or luminal BC, accounting for over 70% of all BC; tumors expressing HER2 are called HER2-enriched BC, accounting for 10-20% of BC; and tumors that do not express ER, PR and HER2 are called triple negative (TN) BC, accounting for 10-15% of BC ( 30 , 73 ). When CDK4/6i were developed and tested in preclinical studies, cell lines and xenografts representing the luminal BC subtype were shown to be most susceptible to proliferation arrest and tumor shrinkage ( 31 , 74 ).…”
Section: Cdk-i and Endocrine Therapymentioning
confidence: 99%
“…In order to assess the general selectivity of palbociclib, we profiled it in lysates derived from the COLO-205 cell line, a cell line known to be sensitive. 11 The profiling was carried out at 10, 1, 0.1, and 0.01 μM, and the results are displayed as a waterfall plot in Figure 3A. The most potent targets are shown in the inset of the waterfall plot, together with the estimated IC 50 values.…”
Section: ■ Resultsmentioning
confidence: 99%
“…COLO-205 cells are sensitive to palbociclib (DNA replication inhibition IC 50 0.13 μM), while MDA-MB-468 cells are resistant (DNA replication inhibition IC 50 > 3 μM). 11 After treatment of the cells with compound, cells were harvested, lysed, probe-labeled, and analyzed by mass spectrometry. The goal of this approach was to evaluate the kinase profiles between the two cells lines in order to understand why COLO-205 cells are sensitive and MDA-MB-468 cells resistant to palbociclib.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations